2019
DOI: 10.1017/prm.2018.124
|View full text |Cite
|
Sign up to set email alerts
|

On quotient modules of H2(𝔻n): essential normality and boundary representations

Abstract: Let D n be the open unit polydisc in C n , n ≥ 1, and let H 2 (D n ) be the Hardy space over D n . For n ≥ 3, we show that if θ ∈ H ∞ (D n ) is an inner function, then the n-tuple of commuting operators (C z1 , . . . , C zn ) on the Beurling type quotient module Q θ is not essentially normal, whereRudin's quotient modules of H 2 (D 2 ) are also shown to be not essentially normal. We prove several results concerning boundary representations of C * -algebras corresponding to different classes of quotient modules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…A detailed study about the two spaces is made in Bickel and Gorkin [11]. It is worth noting that in the polydisc case n ≥ 3, Das, Gorai and Sarkar [23] observed that Beurling type quotient modules H 2 (D n ) ⊖ θH 2 (D n ) is never essentially normal.…”
Section: Essential Normality Of Quotient Modulementioning
confidence: 99%
“…A detailed study about the two spaces is made in Bickel and Gorkin [11]. It is worth noting that in the polydisc case n ≥ 3, Das, Gorai and Sarkar [23] observed that Beurling type quotient modules H 2 (D n ) ⊖ θH 2 (D n ) is never essentially normal.…”
Section: Essential Normality Of Quotient Modulementioning
confidence: 99%